Auditoría Financiera al Gobierno Autónomo Descentralizado Parroquial Rural de Chito del Cantón Chinchipe, Provincia de Zamora Chinchipe. Periodo: 01 de enero al 31 de diciembre del 2015 - Amari Rueda, Elvis Emanuel (2017)
The present thesis work denominated "FINANCIAL AUDIT TO THE AUTONOMOUS GOVERNMENT DECENTRALIZED RURAL PARISH OF CHITO DEL CANTON CHINCHIPE, PROVINCE OF ZAMORA CHINCHIPE. PERIOD 01 JANUARY 31 TO DECEMBER 31, 2015 ", has been made in order to give a contribution to the Parish GAD and d this way better decision-making. In the work, the objectives proposed were evaluated, such as: Evaluate the internal control system implemented by the institution, Verify compliance with legal provisions, Evaluate the components of assets, liabilities, assets, revenues and expenses, through procedures and Techniques applied to the financial statements. In the audit process, there was a lack of procedures to remove assets of the institution that are in poor condition and occupy spaces that could be used for other purposes; The goods do not have the required codification according to the legal provisions, which makes their location and control difficult. xi The audit presents conclusions and recommendations of the work carried out in which the most important is highlighted: Bank reconciliations of the accounts held by the institution are not performed, for which reason it is recommended that the president of the parish GAD appoint a person responsible for the execution of Such reconciliations